KAJIAN EFISIENSI TATANIAGA JENGKOL DI DESA PARDASUKA PRINGSEWU PROVINSI LAMPUNG: STUDY EFFICIENCY COMMERCE JERING IN THE VILLAGE OF PARDASUKA PRINGSEWU, LAMPUNG PROVINCE - Kamilah, Ahya; Lutfiadi, Ridwan; Lukman, Hadi (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2023)
Jengkol or jering (Archidendron pauciflorum, synonyms: A jiringa, pithecellobium jiringa, P.Plobatum) is a plant typical of Southeast Asia. in Malaysia it is called (jering) and Myanmar (da nyin thee). In Thailand it is called (luk nieng) Jengkol including the leguminous tribe (Fabaceae). Jengkol in this case belongs to the fruit group that has not been cultivated optimally. This study aims to determine: (1) the jengkol trading system in Pardasuka Village, Pardasuka District, Pringsewu Regency. (2) jengkol trading system institutions involved in the trading system in Pardasuka Village, Pardasuka District, Pringsewu Regency. (3) how is the efficiency of the jengkol trading system in Pardasuka Village, Pardasuka District, Pringsewu Regency. The results of this study concluded that the jengkol trading channel involved four trading institutions namely farmers, collector traders, wholesalers, retailers. Operationally, of the three existing trading system channel patterns, channel III is more efficient when viewed from the value of the trading system margin which is evenly distributed in each trading system institution involved and seen from the spread of the ratio of profits and costs that is the greatest.